Amorphous calcium phosphate materials: Formation, structure and thermal behaviour. Issue 4 (April 2019) - Vecstaudza, Jana; Gasik, Michael; Locs, Janis
Abstract: Amorphous calcium phosphate (ACP) is essential in formation of mineralized bone and using as a bone substitute. This study presents new aspects of carbonated ACP crystallization during heat treatment. Initially synthesis end pH and drying method (80 °C or freeze-drying) of ACP were varied. Thermal behaviour and structure of differently obtained ACP were evaluated using DSC-TGA, heating microscopy, XRD, FT-IR. In addition, degree of crystallinity (DOC), phase composition and chemical group information were compared for as-synthesized and heat-treated (crystallization end T and 1200 °C) ACP. For the first time DSC-TGA and heating microscopy methods were correlated. DOC of samples dried at 80 °C was synthesis end pH dependent. Heat treatment without temperature hold at crystallization end T produced materials with DOC of 82–91%, thus proving efficiency of low temperature processing. Variations in drying method and synthesis end pH affect structure of the samples heat treated at crystallization end T, but not at 1200 °C.